PENGARUH SOLVABILITAS, UKURAN KOMITE AUDIT, OPINI AUDIT, DAN REPUTASI KANTOR AKUNTAN PUBLIK TERHADAP AUDIT REPORT LAG - Novia Khairunnisa (2021)
The purpose of the study is to analyze how the influence of Solvency, Audit Committee Size, Audit Opinion, and The Reputation of a Public Accountant Firm on Audit Report Lag. By using purposive sampling as a sample collection technique, 243 sample data were generated from 81 companies in the energy sector and transportation and logistics sector listed on the Indonesia Stock Exchange during the 2018-2020 period. Multiple linear regression analysis is a data analysis technique used with panel data regression using STATA 16 and a significance level of 5%. The results show that solvency has a positive effect on audit report lag and audit opinion has a negative effect on audit report lag. Meanwhile, the results also show that the audit committee size and the reputation of a public accountant firm have no effect on audit report lag. The ability of the independent variables and control variables used in this study were able to explain the audit report lag variable of 31.26%, so the other 68.74% were influenced by other factors.